Serum laminin in hepatosplenic human schistosomiasis - E. R. Parise; M. M. B. Leite-Mór; H. Rosa (Memorias do Instituto Oswaldo Cruz, 1992)
Serum laminin level was measured in chronic schistosomiasis. A significant increase in the mean serum laminin levels was observed in patients with hepatosplenic (HS) schistosomiasis (2,57 ± 0,83U/ml), as compared to those in patients with the hepatointestinal (HI) form of the disease (1,38 ± 0,45-U/ml) and in the control group (1,15 ± 0,31 U/ml). In the HS patients there was a significant direct relatiom between serum laminin and percutaneous splenic pulp pressure (r = 0,68). These findigs are compatible with an increased production of lamin in hepatosplenic schistosomiasis with may be related to the observed enlarged liver and spleen basement membranes in such disease.